UNRAVELING THE MENTAL HEALTH OF NURSING PROFESSIONALS: A LOOK THROUGH THE SRQ-20 QUESTIONNAIRE (CIPEEX, 2025)
According to Santos Nascimento (2020), understanding the mental well-being of nurses requires a deep examination of their daily routines, work environments, and individual perceptions. The mental health of nurses is vital for their well-being and workplace performance.This study assessed the mental health of nursing professionals, detecting signs of psychological distress using the Self-Reporting Questionnaire-20 (SRQ-20), which evaluates Common Mental Disorders (CMD) in populations. Conducted via Google Forms and shared through WhatsApp, the study involved 20 nurses (both sexes, aged 22 years or older) from Itapaci and Ceres, Goiás.The results revealed a concerning scenario: 18 out of 20 participants (90%) showed signs of mental distress, while only 2 (10%) reported no emotional or psychological difficulties. The high prevalence of mental distress among nurses highlights the impact of work-related factors such as high workloads, emotional demands, night shifts, and critical decision-making pressures.Interestingly, the 10% of nurses without significant symptoms may represent the presence of protective factors, greater career resilience, or potential underreporting or denial of symptoms.The findings emphasize the urgent need to prioritize mental health support for nurses, fostering a healthy work environment. Early detection and treatment of mental health issues are critical to improving the well-being of nurses and enhancing the quality of patient care. Investments in mental health initiatives for nursing professionals not only improve their quality of life but also contribute to a more productive and supportive work environment.
Keywords: Mental health; Nurses; Well-being; Work environment